A numerical study of strut and tower influence on the performance of vertical axis wind turbines using computational fluid dynamics simulation. Issue 5 (26th January 2022) - Aihara, Aya; Mendoza, Victor; Goude, Anders; Bernhoff, Hans
Abstract: This paper presents the influence of the strut and the tower on the aerodynamic force of the blade for the vertical axis wind turbine (VAWT). It has been known that struts degrade the performance of VAWTs due to the inherent drag losses. In this study, three‐dimensional Reynolds‐averaged Navier–Stokes simulations have been conducted to investigate the effect of the strut and the tower on the flow pattern around the rotor region, the blade force distribution, and the rotor performance. A comparison has been made for three different cases where only the blade; both the blade and the strut; and all of the blade, the strut, and the tower are considered. A 12‐kW three‐bladed H‐rotor VAWT has been studied for tip speed ratio of 4.16. This ratio is relatively high for this turbine, so the influence of the strut is expected to be crucial. The numerical model has been validated first for a single pitching blade and full VAWTs. The simulations show distinguished differences in the force distribution along the blade between two cases with and without struts. Since the wake from the struts interacts with the blades, the tangential force is reduced especially in the downwind side when the struts are considered. The calculated power coefficient is decreased by 43 %, which shows the importance of modeling the strut effect properly for accurate prediction of the turbine performance. The simulations also indicate that including the tower does not yield significant difference in the force distribution and the rotor power.